Immune-Mediated Necrotizing Myopathy Manifesting after Five Years of Statin Therapy - DeRon, Nathan G.; Fischer, Francis; Lopez, Dylan; Brewer, Elizabeth C. (Case Reports in Rheumatology, 2023)
Immune-mediated necrotizing myopathy (IMNM) is an increasingly common and serious condition in which autoantibodies attack muscle fibers causing clinically significant muscle weakness, fatigue, and myalgias. Recognizing the clinical presentation of IMNM is difficult but necessary, as rapid intervention decreases morbidity. We present a case of a 53-year-old female with IMNM induced by statin therapy with confirmed anti-3-hydroxy-3-methylglutaryl coenzyme A reductase antibodies present on serologic testing. The patient’s statin therapy was halted, and the patient was provided with one dose of methylprednisolone and ongoing therapy with mycophenolate. She showed subsequent slow improvements in her muscle weakness and myalgias. It is important for clinicians to be aware of the possible consequences of statin therapy, as these drugs are generally regarded as benign in the medical community. Clinicians should also be aware that statin-induced myopathy can occur at any time during statin therapy. The condition does not necessarily correlate with beginning a new statin medication, as demonstrated in this case in which the patient was on chronic statin therapy before developing symptoms. Continued clinician education and building the fund of medical knowledge regarding this disease are vital to enable clinicians to recognize this disease and act promptly to reduce patient morbidity and improve outcomes.